Gold-catalyzed highly regioselective cage B(9)-H alkylation of o-carboranes with 1,6-enynes - Zheng, Huiyuan; Hao, Yue; Wang, Yongqiang; Zhao, Xue; Zhao, Ximei; Xu, Liang; Hashmi, A. Stephen K.; Wang, Guanghui (Organic letters, 2025)
Described herein is a gold-catalyzed regioselective B(9)-H alkylation of o-carboranes via regioselective insertion of exo-cyclopropyl gold carbenes, generated in situ by gold-catalyzed 5-exo-dig cyclization of 1,6-enynes, into the cage B(9)-H bond of o-carboranes. This new protocol furnishes a broad range of B(9)-bicyclo[3.1.0]hexylmethyl-o-carboranes in moderate to good yields (up to 83%) with good to excellent regioselectivities (B(9)/B(8) up to 100:0). Besides, a gold-catalyzed regioselective cage B(9)-H alkylation of m-carboranes with 1,6-enynes is realized for the first time.
Online veröffentlicht: 15. August 2025
Gesehen am 12.01.2026